The role and Meaning of Managerial Decision in Different Management Schools - Yu. V. Vertakova; A. I. Mandrusova (Управленческие науки)
The unity of conceptual apparatus in all management schools is an essential element for a progressive development of the science. The paper describes the aspect of dividing most resonant theorists of management into schools and the searching for a managerial decision idea in each of those schools. The aim of the work is to develop a generally accepted holistic view of the managerial decision through the analysis of the heritage of the classic theory of management. The research is of a theoretical and general nature, the authors use general scientific methods, including the historical method, analysis and synthesis, methods of analogy and generalization. Here you can find the approach based on the identification of a paradigm including the historical method, analysis and synthesis, methods of analogy and generalization. For the first time, schools of management have been compared from the point of view of their understanding of the essence of management decisions. The paper pays equal attention to the representatives of both world and domestic management theory. The conclusion is about the lack of a common understanding of management decisions shared by all schools. It also revealed the need to formulate its universal idea. As a study result, the sixth school has been added to the five schools identified in management theory. There has been formulated a paradigm for each one including a comparison of schools with respect to their views on a managerial decision. Also, there was compiled a table reflecting ideas about managerial essence and significance in management schools. The results of this research can be useful and relevant both for scientists, involved in management decision-making, and management practitioners who want to reasonably approach the problems and goals facing the organization. The perspective of further research lies in development of a definition that allows to get the most holistic picture of the managerial decision. The complexity of proposing that new definition lies in the need to consider all the achievements of all predecessors and it’s associated with the risk of initial rejection of the innovation by the scientific community.